The Impact of Conducting Research with a First Nation - Darou, Wes G.; Kurtness, Jacques; Hum, Andrew (Canadian Journal of Counselling and Psychotherapy, 2007)
The Cree of northern QuÈbec have had eight psychological studies conducted in their territory. They ejected all the researchers except one. From the point of view of the Cree, the problem appears to be one of behaviour of researchers and respect for an autonomous group. This issue was investigated by conducting an experiment with a group of James Bay Cree from northern QuebÈc. They were then polled as to their reaction to participating in the research. Insensitively conducted research can put major social stresses on both individuals and the community. Several crucial sources of reactivity were found: rigid protocols, requests for self-disclosure, perceived dishonesty, differential treatment of participants, and lack of redeeming social value of the research. These sources of reactivity suggest guidelines for researchers such as respecting local authority, adapting instruments to the culture, and providing feedback to the participants and the community.